Co‐Occurring Extremes of Fine Particulate Matter (PM2.5) and Ground‐Level Ozone in the Summer of Southern China - Yan Lyu; Haonan Wu; Xiaoran Liu; Fuliang Han; Fengmao Lv; Xiaobing Pang; Jianmin Chen (Geophysical Research Letters)
Abstract Concurrent pollution of fine particulate matter (PM2.5) and ozone has been increasingly reported in China recently. Here, we further confirm widespread co‐occurring summertime PM2.5‐ozone extremes in southern China. Annual‐average frequency of co‐occurrence is above 50% from 2015 to 2022, especially in Pearl River Delta region (72 ± 12%). The spatial extent (city numbers) and temporal persistence (co‐occurrence days) for cities with co‐occurrence frequency >50% increase at a rate of two cities/year and 14 days/year, respectively. We further identify typical synoptic conditions (e.g., typhoon periphery circulation, West Pacific subtropical high) conducive to widespread co‐occurrence. Through combining multi‐source data, Random Forest model well predicts PM2.5‐ozone co‐occurrence and identifies common precursors (e.g., volatile organic compounds) as important variables. Finally, we postulate co‐occurrence is linked to synoptic conditions and secondary generation of PM2.5‐ozone from shared precursors. Our results suggest high potentials for co‐occurring PM2.5‐ozone extremes in southern China and control strategies on common precursors to mitigate concurrent pollution.